2020
DOI: 10.5380/ce.v25i0.66744
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento E Atitudes De Profissionais De Enfermagem De Um Hospital Paulista Frente Às Precauções Padrão

Abstract: Objetivo: analisar conhecimentos e atitudes de profissionais de enfermagem sobre adesão àsPrecauções Padrão.Método: estudo descritivo. Amostra composta por 165 profissionais da enfermagem de um hospitalpaulista. Dados coletados pelos Questionnaires for knowledge and Compliance with StandardPrecaution - versão em português e analisados por estatística descritiva com cálculo de frequência.Resultados: a maioria dos profissionais (98,2%) conhece as Precauções Padrão, porém 19,4%responderam corretamente todas as qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(40 reference statements)
0
4
0
2
Order By: Relevance
“…A study conducted in Goiás, Brazil, demonstrated that 30% of nurses reported using such equipment is not common and only uses it sometimes (12) . Most professionals know the standard precautions measures, but the adherence attitude remains partial, and still present a risk behavior by not using masks and goggles (13) .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Goiás, Brazil, demonstrated that 30% of nurses reported using such equipment is not common and only uses it sometimes (12) . Most professionals know the standard precautions measures, but the adherence attitude remains partial, and still present a risk behavior by not using masks and goggles (13) .…”
Section: Discussionmentioning
confidence: 99%
“…The work of health professionals is involved in occupational risk factors that may compromise their physical and mental integrity. This study pays attention to biological risks because, although preventive measures are mandatory in most countries, the number of work accidents with potentially contaminated biological material (WABM) is frequent and worrisome (1)(2) . More than 20 pathogens can be transmitted by exposure to body fluids and cause damage to health.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, low adherence to the use of personal protective equipment (PPE) was also observed (20,22) , such as gloves (15) . Mask use was identified during PIC, although the recommendation is only during insertion of central venous catheters (17) .…”
Section: Care Related To Peripheral Intravenous Catheterism In Pediatrics Performed By Nursing Techniciansmentioning
confidence: 51%
“…In selecting the insertion site, after carefully observing the conditions of the venous network, the professionals started the punctures through the antecubital fossa and subsequently accessed the veins in the hands, similar to other studies (20,22) . According to INS Brazil (16) , the first attempt at PIC should start from the most distal region, considering the particularities of each drug and the possibilities of complications.…”
Section: Care Related To Peripheral Intravenous Catheterism In Pediatrics Performed By Nursing Techniciansmentioning
confidence: 93%